In vitro activity of the ketolide cethromycin in multidrug-resistant clinical Neisseria gonorrhoeae isolates and international reference strains. (4th July 2019) - Jacobsson, Susanne; Alirol, Emilie; Unemo, Magnus
Abstract : Antimicrobial resistance in Neisseria gonorrhoeae is a major public health problem, which compromises the treatment of gonorrhoea globally. We evaluated the in vitro activity of the ketolide cethromycin against a large panel of clinical gonococcal isolates and international reference strains ( n = 254), including numerous multidrug-resistant and extensively drug-resistant isolates. Cethromycin showed potent in vitro activity against most of the gonococcal isolates with the following modal MIC, MIC50 and MIC90 : 0.064 mg/L, 0.125 mg/L and 0.5 mg/L, respectively. However, cross-resistance between azithromycin and cethromycin was identified (Spearman's rank correlation coefficient 0.917) and isolates displaying high-level resistance to azithromycin (MIC >256 mg/L; n = 9) also showed high MICs of cethromycin (32–256 mg/L). In conclusion, the cross-resistance with azithromycin indicates that cethromycin may not be considered for empirical first-line monotherapy of gonorrhoea. However, cethromycin might be valuable in combination antimicrobial therapy and for second-line therapy e.g. for cases with ceftriaxone resistance or allergy.